LIPID PHOSPHATE PHOSPHATASES FROM SACCHAROMYCES CEREVISIAE - Carman, George M. (2007)
DPP(1)-encoded and LPP1-encoded lipid phosphate phosphatases are integral membrane proteins in the yeast Saccharomyces cerevisiae. They catalyze the Mg(2+)-independent dephosphorylation of bioactive lipid phosphate molecules such as diacylglycerol pyrophosphate and phosphatidate. These enzymes possess a three-domain lipid phosphatase motif that is localized to the hydrophilic surface of the membrane. The lipid phosphate phosphatase activities of DPP1-encoded and LPP(1)-encoded enzymes are measured by following the release of water-soluble radioactive inorganic phosphate from chloroform-soluble radioactive lipid phosphate substrate following a chloroform/methanol/water phase partition. The DPP1-encoded enzyme, commonly referred to as diacylglycerol pyrophosphate phosphatase, is purified from wild-type S. cerevisiae membranes by detergent solubilization with Triton X-100 followed by chromatography with DEAE-cellulose (DE(53)), Affi-Gel blue, hydroxylapatite, and Mono Q. The purification scheme yields an essentially homogeneous enzyme preparation that is stable for several years upon storage at −80°. The properties of the DPP1-encoded and LPP(1)-encoded lipid phosphate phosphatase enzymes are summarized.